Music Composition Kulawarga Pencon | Komposisi Musik Kulawarga Pencon - Andika, I Putu Restu; saptono, saptono (GHURNITA: Jurnal Seni Karawitan, 2024)
Kulawarga Pencon is a musical work that summarizes the fusion of two cultural families in instruments based on Balinese and Javanese gamelan. The method for creating Kulawarga Pencon's work adopts the principles stated in the Method for Composing Musical Works (An Alternative) by inserting the process for creating works by I Wayan Beratha. This creation inspired musical processing based on an appreciation of the technique of playing gamelan instruments with pencon and processing rhythms based on various tempos. This approach creates a harmonious intertwining of tones in the formulation of the work. The musical structure of Kulawarga Pencon follows the Tri Angga concept, which consists of kawitan (precursor), pengawak (content), and pengecet (cover). Kawitan is formulated as an introduction that highlights the elements of rhythm, dynamics, and tempo as the basis for the development of the initial part. The crew expanded its scope by developing ancient techniques adapted to the stylist's perspective. The printer is interpreted as the culmination or red thread that transforms the formulation of the work toward the end. The musical work Kulawarga Pencon is composed and structured into three parts with various patterned characters but sourced from existing gamelan with knob techniques adapted to the stylist's interpretation of the interpretive power. This work's result is music processing through a unique mindset and creative process. An experimental result represents the interaction between two cultures, namely Balinese and Javanese Gamelan, in the form of a distinctive instrument, which is then used as a medium for working on the formulation of the work. For 14 minutes, this work was played by 17 musicians, including arrangers, with support from students from the Gamelan Arts Study and Performing Arts Education program at the Indonesian Institute of Arts Denpasar.